Synthesis and Structural Characterization of 4-Hydroxyanilinium 3,4,5,6-Tetrachloro-2-(methoxycarbonyl)benzoate Methanol Monosolvate - Li, Jian (Asian Journal of Chemistry, 2012)
The compound 4-hydroxyanilinium 3,4,5,6-tetrachloro-2-(methoxycarbonyl)benzoate methanol monosolvate (C16H15Cl4NO6, Mr = 459.09) was synthesized and characterized by single crystal X-ray diffraction. The crystal belongs to triclinic, space group P-1, with a = 6.9729(7), b = 10.7860(11), c = 13.5101(15) Å, b = 83.105(2)º, V = 979.49(18) Å3, Z = 2, Dc = 1.557 g/cm3, l = 0.71073 Å, μ(MoKa) = 0.637 mm-1, F(000) = 468. The final refinement gave R = 0.0991, wR(F2) = 0.2400 for 3,338 observed reflections with I > 2s(I). The asymmetric unit of the title compound contains one 4-hydroxyanilinium cation, one 3,4,5,6-tetrachloro-2-(methoxycarbonyl)benzoate anion and one methanol molecule. The two benzene rings are approximately parallel with a dihedral angle of 0.8 (2)º. The components of the crystal are connected, via the intermolecular N-H···O and O-H···O hydrogen bonds interactions, to form network.